Common European Framework of Reference for Languages (CEFR) Standard in Bahasa Indonesia bagi Penutur Asing (BIPA) Textbook: A Competency Mapping Analysis - Fitria, Tira Nur (English Department FBS UNP, 2023)
This research describes the Common European Framework of Reference for Languages (CEFR) in Bahasa Indonesia bagi Penutur Asing BIPA book “Sahabatku Indonesia” especially BIPA Levels A1, A2, B1, B2, C1, and C2. This study applies a qualitative descriptive approach by using a content analysis research design. The analysis shows that the Common European Framework of Reference for Languages (CEFR) is a Common European framework of reference for languages that includes learning, teaching, and language assessment. The CEFR concept is important known and studied by the learners/students and language learners/teachers foreign, especially in the context of learning Indonesian for Foreign Speakers (BIPA). Language Development and Development Agency, through the Center Strategy Development and Language Diplomacy (PPSDK), plays a role important in increasing the function of Indonesian to become an international language. This important role is realized, among others, by supporting language teaching Indonesian for foreign speakers (BIPA) in various countries. One of those supports is the preparation of BIPA teaching materials in the form of “Sahabatku Indonesia” in six book levels A1, A2, B1, B2, C1, and C2. Materials and learning tasks are developed on a text-based basis integrated learners can develop their language competence in the four skills: listening, speaking, reading, and writing various types of text. In addition, learning materials and assignments are designed in an integrated way to be able to develop Indonesian insight. For evaluation purposes, each unit is equipped with a structured task in the form of exercises.